Two complete mitochondrial genomes of extinct form of the Sevan trout Salmo ischchan danilewskii. Issue 1 (2nd January 2018) - Nedoluzhko, Artem V.; Rastorguev, Sergey M.; Simonov, Evgeniy; Boulygina, Eugenia S.; Sharko, Fedor S.; Tsygankova, Svetlana V.; Gabrielyan, Bardukh K.; Roubenyan, Haikaz R.; Levin, Boris A.
Abstract: The mitochondrial genomes from two individuals of the extinct subspecies of the Sevan trout Salmo ischchan danilewskii are published in this paper. The mitochondrial DNA (mtDNA) is 16, 665 base pairs (bp) in length and contained 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. The overall base composition of the genome in descending order was 27.9% of A, 29.4% of C, 16.7% of G, and 26.0% of T without a significant AT bias of 53.9%.